The new facile and straightforward method for the synthesis of 4H-1,2,3-thiadiazolo[5,4-b]indoles and determination of their antiproliferative activity - Belskaya, Nataliya P.; Lugovik, Kseniya I.; Bakulev, Vasiliy A.; Bauer, Jenny; Kitanovic, Igor; Holenya, Pavlo; Zakhartsev, Maksim; Wölfl, Stefan (European journal of medicinal chemistry, 2016)
A series of 4H-1,2,3-thiadiazolo[5,4-b]indoles were synthesized by novel tandem of oxidative cyclization of 3-alkoxycarbonylhydrazonoindoline-2-thiones, 1,5-H-shift and elimination of tert-butoxy(ethoxy)carbonyl group. The simple method for their modifications by the reactions with electrophilic agents were elaborated and as a result of the synthetic investigation a number of N-alkyl-, N-acyl- and N-sulfonyl-4H-1,2,3-thiadiazolo[5,4-b]indoles were prepared in good yields. Preliminary biological tests for the three examples of synthesized compounds with different substituents at the nitrogen atom indole ring have shown that the biological behavior of the investigated 1,2,3-thiadiazolo[5,4-b]indoles is substantially directed by this structural fragment.
Online 11 November 2015
Gesehen am 05.05.2020